Melanoma prevalence: can medical literacy overcome the rise in UV radiation? United States as a case study - Arbel, Yuval; Arbel, Yifat; Kerner, Netanel; Kerner, Miryam (Frontiers in Public Health, 2025)
BackgroundRecent literature shows melanoma prevalence is steadily increasing, mainly due to UV radiation exposure, especially in Caucasians. Skin cancer causes 8.9 billion in direct annual cost and unmeasured indirect costs, but can be prevented by avoiding sun exposure, using protective creams, and regular dermatologists visits for suspicious nevi.MethodsUsing CDC data on non-Hispanic Caucasians, we conducted an Analysis of Variance (ANOVA) to examine the differences in age-adjusted melanoma incidence rates per 100,000. Quadratic Poisson, Ordinary Least Square (OLS) and Two-Stage Least Squares (TSLS) regressions were employed, with UV index and education levels—measured by the percentage of the population holding at least a bachelor’s degree—as key explanatory variables.ConclusionFrom a public policy standpoint, raising awareness about sun exposure protection and encouraging regular examinations by professional dermatologists, especially in sparsely populated areas with high UV radiation—could be crucial in reducing the remarkable costs associated with melanoma morbidity and treatment.